2013
DOI: 10.2967/jnumed.112.115964
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 18F-FDG PET/CT and Diffusion-Weighted MR Imaging as a Predictor of Histologic Response to Neoadjuvant Chemotherapy: Preliminary Results in Osteosarcoma

Abstract: We evaluated the potential of 18 F-FDG PET/CT and diffusionweighted imaging (DWI) to monitor the histologic response in patients with extremity osteosarcoma receiving neoadjuvant chemotherapy, using sequential PET/CT and MR imaging. Methods: We prospectively registered 28 patients with high-grade osteosarcoma treated with 2 cycles of neoadjuvant chemotherapy and surgery. All patients underwent sequential 18 F-FDG PET/CT and MR imaging before (PET/MR1) and after neoadjuvant chemotherapy (PET/MR2). Maximum stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 31 publications
2
59
2
Order By: Relevance
“…Certain studies revealed that an increased ADC following neoadjuvant chemotherapy is associated with good histological response (24,25,27,29,30). However, there have been conflicting results.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Certain studies revealed that an increased ADC following neoadjuvant chemotherapy is associated with good histological response (24,25,27,29,30). However, there have been conflicting results.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, 3 articles were excluded after reviewing the whole article (23)(24)(25). Five articles with 106 patients who fulfilled all of the inclusion criteria were selected for the meta-analysis (Table I) (26)(27)(28)(29)(30). The detailed procedure of study selection and its exclusion reasons in the meta-analysis is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of functional imaging to predict response to chemotherapy in osteosarcomas becomes more vital with our findings, and several groups are investigating the role of PET-CT or functional MRI to preoperatively predict response to neoadjuvant chemotherapy, which may aid the preoperative planning of margins in light of this classification system [8,14]. In particular, it may affect the decision as to the type of surgery planned if the margins are likely to be less than 2 mm and the chemotherapy response is poor because of the probable higher rate of LR after a closer margin.…”
Section: Discussionmentioning
confidence: 99%